Polar cap patch segmentation of the tongue of ionization in the morning convection cell. Issue 12 (20th June 2013) - Zhang, Q.‐H.; Zhang, B.‐C.; Moen, J.; Lockwood, M.; McCrea, I. W.; Yang, H.‐G.; Hu, H.‐Q.; Liu, R.‐Y.; Zhang, S.‐R.; Lester, M.
Abstract [1] Two types of poleward moving plasma concentration enhancements (PMPCEs) were observed during a sequence of pulsed reconnection events, both in the morning convection cell: Type L (low density) was associated with a cusp flow channel and seems likely to have been produced by ionization associated with particle precipitation, while Type H (high density) appeared to originate from the segmentation of the tongue of ionization by the processes which produced the Type L events. As a result, the Type L and Type H PMPCEs were interspersed, producing a complex density structure which underlines the importance of cusp flow channels as a mechanism for segmenting and structuring electron density in the cusp and shows the necessity of differentiating between at least two classes of electron density patches.